2022
DOI: 10.3390/su14137621
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready for a Sustainable Development? A Survey among Young Geoscientists in Italy

Abstract: The United Nations 2030 Agenda is a plan designed to encourage prosperity that is respectful of the planet and its inhabitants. The Agenda will help introduce the concept of education for sustainability (EfS) to a wider population in order to promote inter- and trans-disciplinary knowledge about sustainability. Connecting Earth Sciences (ES) with sustainability allows us to deal with the ethical dimensions and the social implications of this field. The belief is that improving the delivery of knowledge around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In our previous paper [26], illustrating the results of an investigation conducted among young Italian geoscientists on the links between ES and the UN 2030 Agenda, we found that the word "sustainability" is not prominent in the curricula of Italian Earth Sciences departments and that it is conceivable that most students would graduate without having taken a subject course focused specifically on how geosciences can tackle the SDGs and contribute to their fulfilment. Therefore, since it is our belief that the primary objective of the ES community is to put its very important and unique contributions on the floor of the public discussion via an educational program [27], it is crucial to investigate the role of Italian departments in disseminating sustainability education related to geoscience issues.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…In our previous paper [26], illustrating the results of an investigation conducted among young Italian geoscientists on the links between ES and the UN 2030 Agenda, we found that the word "sustainability" is not prominent in the curricula of Italian Earth Sciences departments and that it is conceivable that most students would graduate without having taken a subject course focused specifically on how geosciences can tackle the SDGs and contribute to their fulfilment. Therefore, since it is our belief that the primary objective of the ES community is to put its very important and unique contributions on the floor of the public discussion via an educational program [27], it is crucial to investigate the role of Italian departments in disseminating sustainability education related to geoscience issues.…”
Section: Introductionmentioning
confidence: 71%
“…The annual congress of SGI-SIMP is by far the best occasion to gather together the majority of professionals, researchers, and teachers in geosciences in Italy. With this second questionnaire, the intention was to deepen the analysis about the entanglements between ES and the sustainable development issues, broadening the sample and including not only the young geoscientists [26], but the entire Italian geocommunity. On this topic, the first notable aspect is that, in the face of a much higher number of participants (n = 1086) than in the congress covered by the analysis in our previous article (around 400), the number of answers received was more than the double (110 in the first questionnaire, 229 in the second) but the age ranges most represented were still under 30 (32%) and 31-40 (25.9%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations